Safeguarding National Integrity and Countering Political Divides: A Lesson Learned from Muhammadiyah - Djamal, Samhi Muawan (Universitas Muhammadiyah Makassar, 2023)
This article explores the perspectives of Muhammadiyah, a prominent Islamic organisation in Indonesia, on the preservation of national unity and the resolution of political fragmentation within the country. This research employs a qualitative methodology, using descriptive analysis, to examine, comprehend, and interpret the perspectives of Muhammadiyah, a religious organisation, about their efforts to uphold national unity and address political fragmentation inside Indonesia. The use of a qualitative method was based on the need to get a thorough knowledge of the organisation's opinions and experiences within a complete framework. The idea of Darul Ahdi Wa Syahadah, Muhammadiyah has shown the significant significance of religion-based organisations in fostering unity amidst intricate political dynamics using value-based methodologies, educational initiatives, interfaith dialogue, and community empowerment. The aforementioned results provide valuable insights for many stakeholders on the possible role of religion-based organisations in maintaining social stability and fostering intercommunity collaboration within a dynamic political environment.